ACCOUNTING IN LOCAL WISDOM: REVEALING BARTER TRADITION IN WULANDONI NUSA TENGGARA TIMUR - Marselina, Apriana (Jurnal Sosiologi Dialektika Sosial, 2025)
This study aims to find out two things: first, to understand more deeply about the exchange rate of goods in the barter tradition in Wulandoni District, Lembata Regency, East Nusa Tenggara, and second, to analyze the factors that affect the existence of the barter market in the midst of the circulation of banknotes in the modern century. The type of research used is qualitative descriptive research, which is carried out at the Wulandoni Barter Market. Data were obtained through observation, interviews, documentation, and literature studies. The results of the study show that in barter transactions in Wulandoni District, the exchange rate of goods is determined based on an agreement, without involving money as an intermediary. This barter system uses a traditional rule called "monga" to determine the exchange rate of goods. In addition, factors that affect the existence of this barter market include customary and cultural factors, tena and cotoklema factors, prefo factors, and geographical factors. The barter market has survived because of its harmony with the culture and customs of the local community that upholds traditional values, even though banknotes are widely circulated.